2021
DOI: 10.1007/s00259-021-05340-0
|View full text |Cite
|
Sign up to set email alerts
|

To 1000 Gy and back again: a systematic review on dose-response evaluation in selective internal radiation therapy for primary and secondary liver cancer

Abstract: Purpose To systematically review all current evidence into the dose-response relation of yttrium-90 and holmium-166 selective internal radiation therapy (SIRT) in primary and secondary liver cancer. Methods A standardized search was performed in PubMed (MEDLINE), Embase, and the Cochrane Library in order to identify all published articles on dose-response evaluation in SIRT. In order to limit the results, all articles that investigated SIRT in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
(141 reference statements)
0
17
0
2
Order By: Relevance
“…Most importantly, it suggests that, in most cases, the maximum achievable mean tumour dose has not been reached, a maximum which can only be achieved by microsphere saturation of the tumour microvasculature. This leaves a room for personalized treatment optimization, as an increased tumour dose has been correlated with an improved response rate [9]. Using an image-guided approach, more microspheres could be injected until the point of complete tumour saturation, as long as the healthy liver dose remains below the toxicity threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, it suggests that, in most cases, the maximum achievable mean tumour dose has not been reached, a maximum which can only be achieved by microsphere saturation of the tumour microvasculature. This leaves a room for personalized treatment optimization, as an increased tumour dose has been correlated with an improved response rate [9]. Using an image-guided approach, more microspheres could be injected until the point of complete tumour saturation, as long as the healthy liver dose remains below the toxicity threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment parameters such as injected activity and injection positions are partly based on a treatment simulation, and the resulting absorbed dose distribution is only assessed after treatment. As a result, not all tumours necessarily receive an adequate dose and, indeed, many patients have a suboptimal response to TARE [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible synergetic result may be a radiation-induced inhibition of repair and recovery and increased free radical formation, as observed in animal tumour models with RFA and transarterial chemoembolization (TACE) [ 14 ]. Transarterial radioembolization (TARE) provides an alternative way of delivering adjuvant radiation therapy by means of radioactive microspheres that are administered selectively in the hepatic artery using a high tumour dose and a low toxicity to the healthy liver parenchyma [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar benefit of personalizing the radiation dose was demonstrated in SIRT in the DOSISPHERE-01 trial, leading to both an increase in local response (71% vs. 36%) and survival (26.6 mo vs. 7.1 mo), without an increase in adverse events [12]. Moreover, a lot of research has investigated the doseresponse relation in SIRT and it has been shown that an improved tumour dose leads to an improved response, both in terms of liver progression-free and in overall survival [13].…”
Section: Introductionmentioning
confidence: 99%